Developmental Ecological Psychology meets organicist biology: the example of the ecological self - Catherine Read; Catherine Read; Agnes Szokolszky (Frontiers in Psychology, 2025)
In this paper we outline an ecological-organicist theoretical framework to understand human development. The ecological approach to development (Developmental Ecological Psychology, DEP) places the organism at the center and has a mutualist theoretical framework with an epistemic foundation in direct perception. While research in this tradition has paid much attention to specific developmental questions at a young age (such as perceptual learning, affordances, and action coordination), less effort has gone into the discussion of theoretical issues of overall development at the level of organism-environment mutuality. Meanwhile in biology, a new emphasis on the organism as an explanatory concept and level of analysis has been asserted (e.g., Nicholson, 2014). In this paper, we are seeking possible fruitful ideas at the intersection of the ecological approach and the renewed organicist thinking in biology. We suggest that organicist ideas are relevant for an ecological theory of development and the epistemic foundation of direct perception is important for a consistently mutualist organicism. We examine Waddington’s epigenetic landscape model and Gottlieb’s probabilistic epigenesis from an ecological-organicist point of view and suggest, in contrast, a consistently ecological-organicist approach to self, i.e., the ecological self, based on J.J. Gibson’s idea of co-perceiving self and surround.